Analisis Potensi Lahan Pertanian Pangan Berkelanjutan Di Kabupaten Lamongan Tahun 2018 - Mitha Asyita Rahmawaty (Geo Media: Majalah Ilmiah dan Informasi Kegeografian, 2019)
This study aims to analyze the potential of sustainable food agriculture land in Lamongan District in 2018. This research emphasizes the potential of sustainable food agriculture land based on Lamongan District Regulation Number 15 Year 2011 concerning Spatial Planning for Lamongan Regency in 2011-2031. The research method used is a quantitative research that emphasizes analytical techniques in GIS (Geographic Information Systems), namely overlay and buffering maps. Map overlay is done between the map of agricultural land use with a map of the carrying capacity agricultural land in Lamongan Regency. Then doing a map buffering analysis technique based on road network parameters. The results showed that the potential area for sustainable food agriculture in Lamongan Regency in 2018 was 45,627.54 hectares or 25.17% of the area of Lamongan Regency.